Legumes and cereal crop rotation effect on soil fertility under selected agronomic practices in central farming region, Mongolia - Myagmarsuren, Badamzaya; Begz, Dorj (Proceedings of the Mongolian Academy of Sciences, 2024)
The experimental study aimed at identifying the effects on soil fertility and resources using five different treatments, fallow, non-cultivated land, serial plants, leguminous plants, and grass, was conducted in a central agricultural region of Mongolia. The findings highlight the beneficial effects of cooperative agriculture for food and fodder on the restoration of soil fertility and its resulting useful effect on wheat crop yield. To ensure the stability of soil fertility in the central agricultural region, the key results of the suggest that mobile macro element nitrogen in the soil increased by 45-75.9 per cent over a 3-year rotation with spring soft wheat as the major crop grown along with leguminous plants. Furthermore, the implementation of a two-year rotation of Melilotus albus as intercropping for fodder and food purposes has been found to enhance the rate of soil cellulose decomposition. Furthermore, it has been observed that the continuation of favorable weather conditions and availability of moisture directly correlate with the extent of cellulose decomposition. The aggregate structure of the soil with a diameter of 1-3 mm, which is crucial for growing perennial grass (Agropyron cristatum), is improved by 11.87 per cent to enhance the field's soil structure and reduce erosion. In our research, it was found that legumes have a high protein content and are important role in meeting the needs of livestock and human food, while enriching the soil with nitrogen and increasing the yield of other crops. However, the practical importance of our research lies in the fact that it was established that perennial plants improve the structure of the soil. Legumes, according to our research, are rich in protein and contribute significantly to the provision of food for humans and livestock, as well as to the enhancement of soil nitrogen levels and the growth of other crops. Nevertheless, our study holds practical significance because it proves that grasses enhance the soil's structure as well.